Traditional Decoration in Interior Design - Li , Weifu; Mansor, Noranita (MAJ - Malaysia Architectural Journal, 2023)
Traditional decorative motifs serve as a unique language and symbol that conveys national and regional cultural information from a particular era. They are frequently used in design, particularly interior design, and they not only represent the legacy of traditional culture but also amply illustrate the continued relevance of traditional decorative motifs in the field of interior design. To create works with a distinctively oriental flavor, this paper examines the history and current state of Chinese interior design, researches how to modernize and pass down traditional interior design features, and in-depth analyses of the modern significance of those characteristics. It will enhance the perception of Chinese traditional decorative culture and display the distinctive characteristics of both modern interior design and traditional Chinese decorative art.